2021
DOI: 10.1007/s11540-021-09522-z
|View full text |Cite|
|
Sign up to set email alerts
|

Transplanting Hybrid Potato Seedlings at Increased Densities Enhances Tuber Yield and Shifts Tuber-Size Distributions

Abstract: To contribute to the development of a novel cropping system for potato grown from greenhouse-derived seedlings from hybrid true potato seeds, planting density trials were carried out under normal Dutch agronomic conditions. For two consecutive years, 5-week-old seedlings of two experimental genotypes were transplanted into farmers’ potato production fields at two contrasting locations: a flat-bed system on sandy soil and a traditional ridge system on clay soil. Planting densities were 6.25, 12.5, 25, 50, 100 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 22 publications
(41 reference statements)
1
16
0
Order By: Relevance
“…Likewise, average tuber number was 136 tubers in Est and 199 tubers in Heelsum. The differences in performance between these two trials coincide with previous trials at these same locations (Dijk et al 2021). Trial means for tuber volume were comparatively more stable between trial locations with means of 21.3cm 3 in Est and 24.2cm 3 in Heelsum.…”
Section: Hybrid Estimatessupporting
confidence: 78%
“…Likewise, average tuber number was 136 tubers in Est and 199 tubers in Heelsum. The differences in performance between these two trials coincide with previous trials at these same locations (Dijk et al 2021). Trial means for tuber volume were comparatively more stable between trial locations with means of 21.3cm 3 in Est and 24.2cm 3 in Heelsum.…”
Section: Hybrid Estimatessupporting
confidence: 78%
“…In recent years, the use of field transplanted, nursery-raised, hybrid potato seedlings has been tested as a potential alternative system for seed and ware potato production [ 54 ]. Ultimately, to obtain a highly productive transplanted crop, aspects of seedling production, field establishment and transplant field crop management need be considered and successfully executed [ 55 ]. These aspects include, but are not limited to, nursery climatic conditions and nursery management factors, field conditions at transplanting (soil and climatic conditions) and crop management factors, all of which, when successfully carried out, contribute to high productivity in transplanted crops [ 53 ].…”
Section: Cropping Systemsmentioning
confidence: 99%
“…The longer duration of the growing season was one observation from the transplanting moment study that became apparent. The timing of harvest was of some maturity types more important than the timing of -or conditions during- transplanting [ 55 ]. With these studies, we have shown the feasibility of the field transplanted systems.…”
Section: Cropping Systemsmentioning
confidence: 99%
See 2 more Smart Citations